Micromechanisms of failures in ultralight magnesium alloys - Mark, Chee Kong (2010)
Failure is always a potential problem to engineers whenever materials are used. Much effort has been directed towards the development of satisfactory fracture criteria to enable structural engineers to design confidently against such possible failures. However, so far understanding of failures in many materials is quite poor, although considerable knowledge has been obtained on failure mechanisms of steels. The project, therefore, aimed to gain better understanding of deformation and fracture processes in those engineering materials whose fracture mechanisms are poorly understood. Two ultralight magnesium alloys AZ91D and AMSOA were chosen for the study due to their importance to engineering applications. In this project, a technique was developed to combine the capabilities of optical microscope or SEM and mechanical testing device. A microtensile tester was installed under the optical microscope or inside an SEM to make it possible to carry out in-situ observation of deformation and fkacture processes when the tensile test is going on. The testing results for notched specimens of AZ91D magnesium alloy with different notch angles show that the smaller the notch angle, the higher the fracture stress level. This is quite unexpected, but the phenomenon observed can be explained in terms of sampling process. Small notch angle leads to localized plastic deformation zone and therefore makes it less likely to "sample" large defects in the magnesium alloy.